Raising of adolescents in the era of reality shows and tabloid journalism - legal regulation - Slavković, Ana V.; Slavković , Vukan R. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2023)
The authors seek to answer why the criminals in media are presented in a way that does not meet the reality, which categories of young people are at the most risk considering the negative impact of this , role models“, and how the family and legislation can protect them. Behind the media presentation of the crime world as idyllic are the centers of power, which are in agreement with the owners of the media, with the aim to form insecure personalities, prone to addictions, who looks up to inadequate role models. For the proper development of adolescents, close relationships with parents and peers are necessary. Parents represent a safe haven when peer and other social relations do not go in the desired direction. In contact with peers, adolescent learns new roles, about the world of adults, and finds a new type of egalitarian closeness. A close relationship with parents allows the young person to discuss role models from media, positive and negative heroes, values, dilemmas, events in peer relationships, and plans for the future, as well as to convey life experiences from parent to adolescent. On the other hand, legislation is necessary to protect social groups from media exploitation or exposure to media violence.